Closing the gap between graduates' skills and employers' requirements: A focus on the strategic management capstone business course - Meredith E. David; Fred R. David; Forest R. David (Administrative Sciences, 2021)
Strategic management has long been the capstone course for business majors at most colleges and universities globally. As originally designed, the capstone course sought to teach students an array of skills and tools needed to actually perform strategic planning, primarily through integration and application of functional business concepts and techniques. Times have changed, however, and business schools have come under scrutiny regarding their ineffectiveness in developing graduates' skills commensurate with employers' requirements. Such criticism is justified as academics teaching the capstone business course have partitioned their instruction efforts to focus increasingly on theory rather than practical applications. After a pertinent evaluation of current academic research, we illuminate how and why increased focus on practice is needed in strategic-management pedagogy. We delineate how the once well-designed business capstone course has evolved into a course that too often fails to impart practical competencies to graduating students. To facilitate closing the gap between graduates' skills and employers' requirements, we present a strategic management pedagogical model designed to promote student learning and development of hard and soft skills related to actually doing strategic planning. The proposed model can help reduce the gap between graduates' skills and employers' requirements with the intended purpose to provide increased interest for teaching practical tools that were developed by practitioners. Such tools include the BCG matrix, developed by the Boston Consulting Group, and the Internal-External (IE) portfolio matrix derived from the General Electric (GE) Business Screen developed by Jack Welch, former CEO of GE. The proposed model also reveals the process of including both internal and external aspects into strategic decision making as evidenced by countless organizations performing Strength-Weakness-Opportunity-Threat (SWOT) analyses. The proposed model significantly enhances previous theory-based approaches for teaching the capstone strategic-management course.
Keywords: 350; strategic management; business pedagogy; employability; management competencies; teaching strategy; strategic planning; capstone course; case analysis; applying tools and skills